Influence of repeated impact of transport loads on the deformation characteristics of the soil foundation of highways: Influence of repeated impact of transport loads on the deformation characteristics of the soil foundation of highways - Бекенов, Тасыбек; Аубакиров, Баубек; Бектегенова, Алия (Рroblems of engineering and professional education, 2022)
-